2020
DOI: 10.26858/ijole.v4i2.12441
|View full text |Cite
|
Sign up to set email alerts
|

TPACK Model Based Instruction in Teaching Writing: An Analysis on TPACK Literacy

Abstract: Acknowledging prior knowledge on technology, pedagogy, and content of lecturers in this early stage of developmental research is assuming important as basic data for further steps in designing TPACK model-based instruction in teaching writing. Therefore, having investigation on TPACK literacy of the lecturers will complete the data needed in this study. This paper presents an analysis of Technological Pedagogical and Content Knowledge (TPACK) literacy among lecturers at Universitas Muhammadiyah Parepare, Indon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
25
0
6

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(35 citation statements)
references
References 1 publication
4
25
0
6
Order By: Relevance
“…Yet, the result on this study will not be eternal and final since it is assumed that the new transformation of online learning will be come a new culture several years later then teachers in Indonesia accustomed with it (Wijaya et al, 2021). On the other hand, although, finally from this study we know that EFL Indonesian willingness level in TPACK in middle, same like their level in TPACK itself, it is impossible to say that all instructors with varying levels of experience have the same level of willingness to comprehend and execute their TPACK (Ammade et al, 2020;Cahyono et al, 2016;Surayya & Asrobi, 2020). Thus, the result of the questionnaire used in this study may be different if it is applied in the other language area where technology become an alter ago, like IT teachers, or even economic, law, science, or health area.…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…Yet, the result on this study will not be eternal and final since it is assumed that the new transformation of online learning will be come a new culture several years later then teachers in Indonesia accustomed with it (Wijaya et al, 2021). On the other hand, although, finally from this study we know that EFL Indonesian willingness level in TPACK in middle, same like their level in TPACK itself, it is impossible to say that all instructors with varying levels of experience have the same level of willingness to comprehend and execute their TPACK (Ammade et al, 2020;Cahyono et al, 2016;Surayya & Asrobi, 2020). Thus, the result of the questionnaire used in this study may be different if it is applied in the other language area where technology become an alter ago, like IT teachers, or even economic, law, science, or health area.…”
Section: Discussionmentioning
confidence: 65%
“…To be more specific, teachers' TPACK on writing are in moderate level. If teachers' TPACK is examined in a broad sense, it suggests they have a decent degree of TPACK, but it is difficult for them to adapt their specialized content knowledge to specific technology (Ammade et al, 2020;Surayya & Asrobi, 2020). The findings revealed that Education Technology graduates possessed a strong grasp of subject and pedagogical competence (Utama's, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Theoretically, this study is anchored on some assumptions based on two models of technology, which include Technological Pedagogical Content Knowledge (TPACK) and Technology Acceptance Model (TAM). First, TPACK framework is built upon Shulman's idea of Pedagogical Content Knowledge to describe how teachers' understanding of educational technologies and PCK interrelate with each other to come up with an effective teaching with the use of technology (Ammade et al, 2020;Hossain et al, 2019). TPACK framework is the intricate interaction between and among the primary forms of knowledge: (i) content (CK); (ii) pedagogy (PK) and; (ii) technology (TK).…”
Section: Review Of Literaturementioning
confidence: 99%
“…Ding et al (2019) and Tseng et al (2019) identified that teachers could use technologies to motivate students to learn. Ammade et al (2020) identified that it is hard to assert that all teachers with varying degrees of expertise are equally motivated to learn and use the TPACK framework.…”
Section: Portraying Consistencies and Inconsistencies Of Teachers' Be...mentioning
confidence: 99%
“…Emerging the TPACK framework is embedded within a particular discipline and context. Teachers may use the TPACK framework to build online resources and evaluations while enhancing teaching quality to enable students to take accountability for their learning experiences (Ammade et al, 2020). Given that teachers must be able to work and study online regardless of the reason or scenario, COVID-19have an immediate and enduring effect on their TPACK framework in the future (Fuad et al, 2020).…”
Section: Introductionmentioning
confidence: 99%